The portfolio of evidence as a qualification modality in the Normal Schools - Dino-Morales, Laura Irene; Tobón, Sergio (IE Revista de Investigación Educativa de la REDIECH, 2017)
The purpose of the following documentary research was to reflect about the importance and use of the portfolio of evidence as a mode of qualification in normal schools; this implies that the future teacher reflects and analyzes his formation and development of professional competences, by linking them with his teaching practices. The methodology used consisted in a documentary analysis, as well as the use of conceptual cartography to direct the work to be done. The results obtained allowed to identify the idea of portfolio of evidence from the social-formative approach as a process that joints didactic with assessment, and is focused on talent development from the continuous improvement of evidence. It was possible to determine the following axes in the portfolio methodology: competences selection, evidence determination, evidence systematization, assessment, reflection and analysis, socialization and certification. It is suggested to validate the proposed methodology from the socio-formation and to develop an analytic rubric that enables the appraisal of student’s portfolios as a qualification modality in normal schools.